Pengembangan Media Pembelajaran Monopoli pada Materi Pertumbuhan Hewan di Sekolah Dasar - Nugraha, Frengki Arya; Junaidi, Ilham Arvan; Ayurachmawati, Puji (Indonesian Research Journal on Education, 2022)
The learning method at SD Negeri 195 Palembang is monotonous and unpleasant. The teacher has never developed a monopoly learning media on animal growth material for class III Elementary School. The monopoly media that has been used does not yet exist in the material for animal growth for grade III Elementary School. The purpose of this study was to determine thedevelopment of monopoly learning media on animal growth materials in elementary schools. This research method uses research and development methods with the limits of expert judgment and practicality. Expert assessment is carried out on media, language, and material experts, while practicality is with teachers and students. Data collection techniques use documentation and questionnaires, while data analysis techniques use proportions. The results of the expert's assessment show that the learning media is monopoly with a percentage of 88.65%. Thus, it can be said that the development of monopoly learning media on animal growth materials for grade 3 SD is included in the very valid or very feasible category. From the results of the skills of teachers and students obtained by 90.19%. Thus, it can be said that the practicality of monopoly learning media in grade 3 elementary school learning is included in the very practical category.